Chapter 31 Political risks and nationalism - Kurosawa, Takafumi (Taylor & Francis, 2017)
This chapter analyses risks arising from political phenomena including nationalism. Such "non-market risks" include political as well as natural disasters. Taking an historical perspective, the authors interrogate several key research questions, including: What impact did political risk and nationalism have on global business? Have wars and other conficts caused by national interests and identities retarded or even reversed the trend towards globalization? When faced with political and geopolitical threats such as war, occupation, expropriation, economic blockade and sanctions, requisition, persecution, or boycott, how did multinational enterprises (MNEs) and other international economic actors manage (or fail) to overcome the situation they found themselves in? How did the response of economic entities like MNEs transform global business, or change political risks and the sovereign state system? Fundamentally, the chapter shows how the examination of such phenomena provides key insights into business history and international business research.